The Control of the Body: The Allegation of Witchcraft in the Memoriale of Flaminio Parisio, Bishop of Bitonto, 1594 - Romano, Francesca Vera (Louvain studies, 2023)
The paper examines the concept of female corporeality in relation to witchcraft and possession through the Memoriale of Flaminio Parisio, bishop of Bitonto, written in 1594. Parisio sought to justify to the Holy Office the trials, tortures, and violent exorcisms carried out by himself and archdeacon Ottavio Bovio against women accused of witchcraft and apostasy. The Memoriale was written in response to a cardinal’s inquiry, likely Giulio Antonio Santoro, while a commission investigated Parisio and Bovio for violating legal principles by denying the accused a proper defense and appeal to Rome during the 1594 trials. The alleged witches, likely lower-class women, prostitutes, or midwives, were subjected to extreme violence based on demonological treatises, as their bodies were perceived as sites of demonic possession. The document, rich in juridical references, highlights the construction of witchcraft accusations and the control of the female body as a symbol of the devil’s influence.